Indonesian Government Strategies On Obtaining Crude Palm Oil (CPO) Market Access To European Union Countries Over The EU Parliament Resolution On Palm Oil And Deforestation Of Rainforest - Bustanul Arifin; Komang Audina Permana Putri (Department of International Relations, Universitas Andalas, 2019)
Indonesia is the largest producer of palm oil in the world. With Malaysia, palm oil production could account for about eighty percent of global production. Meanwhile, Europe is the country with the third largest CPO export destination for Indonesia after India and China. However, the EU proposed a European Union resolution initiative on palm oil and deforestation of rainforest, which finally passed with the major votes from EU members of Parliament in April 2017. The key point on EU resolution reveals that EU will ban palm oil use for biofuels production by 2020. The purpose of this research is to analyze the Indonesian government’s diplomatic efforts to respond and negotiate with EU regarding the issue. It is also considered important to prevent the global downturn on palm oil products. To analyze the diplomacy effort, the researcher will use qualitative methods presented through data collection from sources such as books, journals, press releases and official reports from institutions in this case the European Union. To support the research, the researcher also uses primary data through the interview with one of the representative of the Ministry of Foreign Affairs of the Republic of Indonesia for diplomatic actions conducted by Indonesian government. This research finds that the government of Indonesian finally combined several soft diplomatic strategies to face EU both directly and indirectly.Keywords: Strategies, Government of Indonesia, Trade, Palm Oil, EU Resolution, Deforestation